Locative Media and Identity: Accumulative Technologies of the Self. (August 2016) - Saker, Michael; Evans, Leighton
The role of location-based social networks (LBSNs) on identity is a relatively unexplored area within the growing cannon of work on locative media. Following an exegesis of Giddens's argument that narrative biographical accounts are critical in self-identity in the modern age and Foucault's technologies of the self, this article positions LBSN, and in particular Foursquare, as a contributor to self-identity in users' lives. A close reading of ethnographic and interview data from Foursquare users reveals that in the context of the presentation, maintenance, and reflection upon self-identity, LBSN use can play an integral role in the self-identity of its users. The contribution of LBSN to indicators of user lifestyle, the intentional sharing of particular locations, and user recollection of events and locations are the key features of how LBSNs provide conduits to self-identity. The degree of usage in everyday life is identified as critical in the positioning of LBSN as a key contributor to identity narratives. With the integration of LBSN features into more mainstream social media platforms, this contribution to self-identity in the social media age is resilient to the demise of stand-alone LBSN applications.